Environmental noise perception by students and teachers and simulation of the Speech Transmission Index - Loro , Carmen Lucia Pezzette; Nascimento, Eriberto Oliveira do; Zannin, Paulo Henrique Trombetta (National Journal of City Management, 2021)
As diverse as the knowledge transmission techniques aided by multimedia resources are, nothing replaces the teacher-student relationship, which is developed in the classrooms. Therefore, classrooms must offer the necessary conditions for the satisfactory development of teaching and learning activities. In this context, the importance of classroom acoustics is highlighted. The Speech Transmission Index (STI) is one of the broadest and most important parameters to measure speech intelligibility. STI weighs the effects that can cause deterioration on the voice signal, such as the reverberation time and background noise. This work presents an evaluation of the acoustic performance of classrooms using the STI. For that, three constructive patterns were evaluated. The constructive models were named 010, 022 and 023. Students and teachers answered a questionnaire about the perception of noise in the classroom and at school, and the constructive pattern 023 was studied. Computer simulations were performed with ODEON software to precited STI. The results of the measurements and the questionnaires revealed that the noise that disturbs the activities in the classroom comes from the school itself, not only from the other classrooms, corridors and adjacent patios, but also from inside the classroom itself.